2019
DOI: 10.1186/s12879-019-3948-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for death among children 0–59 months of age with moderate-to-severe diarrhea in Manhiça district, southern Mozambique

Abstract: Background Despite major improvements in child survival rates, the number of deaths due to diarrhea remains unacceptably high. We aimed to describe diarrhea-associated mortality and evaluate risk factors for death among Mozambican children with moderate-to-severe diarrhea (MSD). Methods Between December 2007 and November 2012, children under-five with MSD were enrolled in Manhiça district, as part of the Global Enteric Multicenter study (GEMS). Clinical, epidemiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 46 publications
4
52
0
Order By: Relevance
“…In Mozambique, G. duodenalis has been described at infection rates of 1-6% by conventional microscopy in paediatric and clinical populations in Maputo province [31][32][33], and of 8-37% by PCR in patients with HIV and/or tuberculosis in Gaza province and people living in a high endemic area of Sofala province [21,25]. Using enzyme-linked immunosorbent assay (ELISA), G. duodenalis was identified in 10-50% of children with clinical manifestations in different provinces of the country [34][35][36]. The G. duodenalis crude prevalence rate found here (42%) is in the upper range limit of those reported in the aforementioned surveys.…”
Section: Discussionmentioning
confidence: 99%
“…In Mozambique, G. duodenalis has been described at infection rates of 1-6% by conventional microscopy in paediatric and clinical populations in Maputo province [31][32][33], and of 8-37% by PCR in patients with HIV and/or tuberculosis in Gaza province and people living in a high endemic area of Sofala province [21,25]. Using enzyme-linked immunosorbent assay (ELISA), G. duodenalis was identified in 10-50% of children with clinical manifestations in different provinces of the country [34][35][36]. The G. duodenalis crude prevalence rate found here (42%) is in the upper range limit of those reported in the aforementioned surveys.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 Moreover, poor socioeconomic status, large family size, previous experience of child illness and death; poor educational status of caregivers, low maternal and child health services utilization; low coverage, and poor quality of primary health care services were the foremost commonly mentioned factors affecting child feeding practices during and after diarrheal disease. 22 , 23 A study done in that of rural pastoralist communities of the Afar region, Ethiopia showed, only 5.2% of children with diarrhea were offered foods more than usual. 23 In spite of multiple site-specific studies, national-level studies would also have a paramount contribution to the achievement of the national target regarding child health, however, child feeding practices and associated factors during diarrheal disease is remained unstudied in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in Manhiça district, southern Mozambique, showed an association between diarrhoea and undernutrition [ 13 , 14 ]. During 10 years of surveillance, 47% of the hospitalized children presented one or more types of undernutrition, of which 6% were severely undernourished [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…During 10 years of surveillance, 47% of the hospitalized children presented one or more types of undernutrition, of which 6% were severely undernourished [ 13 ]. Also in the same area, another study reported undernutrition as one of the risk factors for mortality in children with moderate-severe-diarrhoea [ 14 ]. To date, most studies of diarrhoeal diseases took place in southern Mozambique, with few studies conducted exclusively in northern provinces [ 15 ].…”
Section: Introductionmentioning
confidence: 99%